FORMAÇÃO SERRA DA BOCAINA - CONTRIBUIÇÃO DO VULCANISMO PALEOPROTEROZOICO DO ARCO MAGMÁTICO AMOGUIJÁ NO TERRENO RIO APA, SUL DO CRÁTON AMAZÔNICO - Souza, Cinthya Deus; Sousa, Maria Zélia Aguiar; Ruiz, Amarildo Salina; Batata, Maria Elisa Fróes; Brittes, Ana Flávia Nunes; Lafon, Jean Michel (Geochimica Brasiliensis, 2017)
The Serra da Bocaina Formation comprises Paleoproterozoic effusive and pyroclastic rocks displaying well preserved textures related to a plutonic-volcanic event recorded in the southern of the Amazonian Craton in the Rio Apa Terrane. This record sits in the São Francisco Hill, municipality of Porto Murtinho, southwestern of the Brazilian state of Mato Grosso do Sul. Geological and petrographic analyses allowed to distinguish between effusive volcanism represented by subaerial coherent volcanic deposits that occur as rhyolite flows, and explosive volcanism that is represented by ignimbrite deposits among which three distinct facies are recognized: Lithic Ignimbrite, Crystal-rich Ignimbrite, and Ignimbrite Tuff. The explosive rocks show diagnostic features of deposition of pyroclasts under high temperatures, and were likely formed in caldera settings. Geochemically, these rocks are compatible with subalkaline, peraluminous and ferrous magmatism as well as show calc-alkaline affinities. A U-Pb (SHRIMP) zircon crystallization age of 1899 ± 9 Ma was obtained for the rhyolite flows. The data obtained suggest a large magnitude for the volcanism that gave rise to the Serra da Bocaina Formation, which has already been described by other authors and is an important Orosirian record of the evolutionary history of the Amoguijá Magmatic Arc.